Elective neck dissection in metastatic cutaneous squamous cell carcinoma to the parotid gland: A systematic review and meta‐analysis. Issue 4 (7th December 2018) - Rotman, Anthony; Kerr, Stephen J; Giddings, Charles E B
Abstract: Current management of metastatic cutaneous squamous cell carcinoma (CSCC) to the parotid is surgical excision and postoperative radiotherapy. In the node‐negative neck, there is debate about the role of elective neck dissection (END), irradiation or observation. This systematic review assesses the prevalence of occult cervical disease and the evidence for END. A literature search was performed using Medline and Embase. All papers describing management of the neck in metastatic CSCC to the parotid were assessed for inclusion. Eighty‐nine papers were identified and 17 met inclusion criteria. A total of 874 ENDs were performed in 874 patients with metastatic CSCC to the parotid with no clinically evident cervical disease. The overall prevalence of occult disease in a random effects model was 22.5% (95% confidence intervals 18.9‐26.0). The prevalence of occult cervical disease in metastatic CSCC to the parotid is high. END is recommended in this patient group.